Investigation of Cytotoxic Constituents from Seed Pulp of Entada Phaseoloides and Metabolite Profiling Using UPLC-QTOF-MSE. (30th September 2020) - Pavan Kumar, P; Siva, Bandi; Katragunta, Kumar; Beedkar, Supriya D; Ramakrishna, Sistla; Barua, Chandana C; Suresh Babu, K
Abstract: Background: Entada phaseoloides (Linn.) Merr. (Family: Fabaceae) is a well-known, traditional, medicinal plant that has been extensively used in the Ayurvedic system of medicine for centuries to combat a wide range of ailments. Objective: The goal of this work was to investigate the bioactive constituents from n -butanol extracts of Entada. phaseoloides and develop a method for the comprehensive characterization of saponins using liquid chromatography with an electrospray ionization quadrupole time-of-flight mass spectrometer (LC-ESI-QTOF-MS). Methods: A hyphenated technique, ultra-performance liquid chromatography quadrupole time-of-flight mass spectrometry (UPLC-QTOF-MS/MS), has been proposed to integrate LC and MS together with NMR for structural elucidation. This method allowed comprehensive characterization of saponin glycosides from E. phaseoloides based on their MS/MS fragmentation study. Results: The phytochemical study of E. phaseoloides resulted in the isolation and identification of three bio-active constituents. Further, the UPLC-QTOF-MS/MS method led the structure elucidation of saponin constituents directly from crude extracts via comparison of the exact molecular masses from their MS/MS spectra. Identified common fragments m/z 648, 630, 498, 366, and 204 were used for the screening of saponin components. Conclusions: The present study summarizes the isolation and identification of bio-compounds from n -butanol extract and the demonstration of UPLC-QTOF-MS/MS analysis for the characterization of compounds in complex crude extracts. To the best of our knowledge, this is the first systematic study in structural characterization on complex saponins and other metabolites from crude extract of E. phaseoloides using UPLC-ESI-QTOF-MS E . Highlights: Rapid analysis and characterizations of three new saponins from E. phaseoloides using UPLC - ESI-QTOF-MS E were tentatively identified based on the mass fragmentation study.